Study of Waste Management in Jambi City - Yulia Harnila; Asmadi Saad; Edison Edison (Universitas Jambi, 2022)
Research was conducted in Jambi City from August 7 to September 27 2016. While the reason of choosing location of research was because the Department of Gardening and Cemetery Cleaning Jambi City is a government agency in the City of Jambi which deal with cleanliness issues that include the waste management in the city of Jambi. This research was analyzed by using Analytical Hierarchy Process (AHP) approach. The AHP was used to analyze waste management alternatives based on social, economic, environmental and technological aspects. The research used interview technique and questionnaire. From the research result showed that garbage fleet capability was not optimal yet. Rotational trucking using the current Arm Roll Truck was 6 rit / day, which this value had exceeded the limits of a 4-rit / day / truckload capability. Meanwhile, garbage trucking by using Dump Truck and Typer truck could still be upgraded again to 3 trips per day. Ability to transport the existing waste was also affected by the condition and age of the vehicle. The location of TPS placement or strategic container was on the land belonging to the Municipal Government, somewhat away from the settlements, could be traveled by the trucking vehicle and trash could not be more than one day (24 hours). Meanwhile, the effort of garbage solving doing by the appropriate institution in garbage management got varied result from less good until good enough.